Subclinical Doses of Combined Fumonisins and Deoxynivalenol Predispose Clostridium perfringens–Inoculated Broilers to Necrotic Enteritis - Shanmugasundaram, R.; Adams, D.; Ramirez, S.; Murugesan, G. R.; Applegate, T. J.; Cunningham, S.; Pokoo-Aikins, A.; Glenn, A. E. (Frontiers in Physiology, 2022)
Fumonisins (FB) and deoxynivalenol (DON) are mycotoxins which may predispose broiler chickens to necrotic enteritis (NE). The objective of this study was to identify the effects of subclinical doses of combined FB and DON on NE. A total of 480 day-old male broiler chicks were divided into four treatment groups; 1. Control group (Basal diet + Clostridium perfringens); 2. Necrotic enteritis group (Basal diet + Eimeria maxima + C. perfringens); 3. FB+DON group (Basal diet + 3 mg/Kg FB + 4 mg/Kg DON + C. perfringens); and 4. FB+DON+NE group (Basal diet + 3 mg/Kg FB + 4 mg/Kg DON + E. maxima + C. perfringens). Birds in NE and FB+DON+NE groups received 2.5 X 103 E. maxima on d 14. All birds were inoculated with C. perfringens on d 19, 20, and 21. On d 35, birds in the NE, FB+DON, and FB+DON+NE groups had 242, 84, and 339g lower BWG and a 19, 2, and 22 point increase in FCR than in the control group. Subclinical dose of FB+DON increased (P < 0.05) the NE lesion scores compared to the control group on d 21. On d 21, birds in the NE, FB+DON, and FB+DON+NE groups had increase (P < 0.05) in the serum FITC-D, respectively, lower (P < 0.05) jejunal tight junction protein mRNA, and increase (P < 0.05) in cecal tonsil IL-1 mRNA compared to control group. On d 21, birds in the NE group had decreased (P < 0.05) villi height to crypt depth ratio compared to the control group and the presence of FB+DON in NE-induced birds further decreased the villi height to crypt depth ratio. Birds in the NE, FB+DON, and FB+DON+NE groups had increased (P < 0.05) C. perfringens, lower (P < 0.05) Lactobacillus loads in the cecal content and a lower (P < 0.05) CD8+: CD4+ cell ratio in the cecal tonsils compared to the control group. It can be concluded that subclinical doses of combined FB and DON predispose C. perfringens-inoculated birds to NE, and the presence of FB+DON in NE-induced birds exacerbated the severity of NE.